Associations between maternal eating behaviours, feeding practices, and infant appetitive traits in Malaysia - Mok, Kai Ting; Nurliyana, Abdul Razak; Kaur, Satvinder; Gan, Wan Ying; Loy, See Ling (Academic Press, 2025)
Appetitive traits developed in infancy may influence dietary habits in later childhood. The impact of maternal eating behaviours (MEBs) and feeding practices remains unclear. This cross-sectional study examined the associations between MEBs, feeding practices, and appetitive traits of infants aged 1–6 months in Malaysia. A total of 256 mother-infant pairs were recruited from six government maternal and child health clinics in Kuala Lumpur and Putrajaya. Data were collected through self-administered questionnaires: the Dutch Eating Behaviour Questionnaire (DEBQ) to assess MEBs (emotional, external, and restrained eating); the Baby's Basic Needs Questionnaire (BBNQ) to evaluate feeding practices (feeding modes and feeding-to-soothe (FTS)); and the Baby Eating Behaviour Questionnaire (BEBQ) to measure infants' appetitive traits (food responsiveness, enjoyment of food, satiety responsiveness, slowness in eating, and general appetite). The mothers' mean age was 32.31 ± 4.45 years, and the infants' mean age was 3.73 ± 1.67 months. Food responsiveness of formula-fed infants (14.33 ± 4.82) was significantly lower than breastfed (17.99 ± 5.33). Restrained eating was significantly associated with higher satiety responsiveness (B = 0.206, 95 % CI = 0.022–0.099), and FTS was linked to increased food responsiveness (B = 0.334, 95 % CI = 0.116–0.241). These findings highlighted the associations between MEBs and FTS with infant appetitive traits. Longitudinal studies are needed to clarify these relationships and their long-term implications.